A character art generator using the local exhaustive search, with GPU acceleration. Issue 1 (2nd January 2016) - Takeuchi, Yuji; Nakano, Koji; Takafuji, Daisuke; Ito, Yasuaki
Abstract : An ASCII art is a matrix of ASCII code characters that reproduces an original grey-scale image. A JIS art is an ASCII art that uses JIS Kanji code characters instead of ASCII code characters. They are commonly used to represent pseudo grey-scale images in text -based messages. Since automatic generation of high quality ASCII/JIS art images is very hard, they are usually produced by hand. The main contribution of this paper is to propose a new technique to generate an ASCII/JIS art that reproduces the original tone and the details of an input grey-scale image. Our new technique is inspired by the local exhaustive search (LES) to optimise binary images for printing based on the characteristic of the human visual system. Although it can generate high quality ASCII/JIS art images, a lot of computing time is necessary for the LES. Hence, we have implemented our new technique in a graphics processing unit (GPU) to accelerate the computation. The experimental results show that the GPU implementation can achieve a speedup factor up to 89.56 over the conventional CPU implementation.